Assessment of Demand and Supply of Livestock Feed and Fodder Resources in Rajasthan - Meena, G.L.; Mishra, Siddhartha; Chand, Prem (Indian Journal of Animal Nutrition, 2018)
Supply and demand of animal feed and fodder resources in Rajasthan was estimated by using secondary data of triennium ending (TE) 2013-14 on land utilization pattern, crop production and livestock population. The annual supply of feeds and fodders in the state was estimated to be 60.11 m tonnes on DM basis as against the demand of 76.27 m tonnes showing a net deficit of 16.15 m tonnes (approximately 21% per annum). The Rajasthan state had a potential DM supply of 60.11 m tonnes of which crop residues, green roughages and concentrates accounted for 60.91, 27.99 and 11.10%, respectively. Within the crop residues, green roughages and concentrates groups, the cereals (73.90%), cultivated fodders (75.59%) and oil cakes (48.75%) had the major share. The study clearly showed that scarcity of feeds and fodders is a major constraint for low production and productivity of animals in the state. For sustainable livestock production in Rajasthan, the improved cultivated and management practices of all the fodder resources along with fodder conservation and utilization strategy need to be developed.